(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Microfinance programmes are promoted as a key strategy for simultaneously addressing both women empowerment and poverty alleviation. However, there has been a hot debate on the potency of microfinance in empowering the women. Apparently, this research was conducted to study the impact of microfinance services on the economic and social empowerment of women. Women empowerment is depending on their economic empowerment. When they are economically empowered, the women will have the sky as limit.